2014
DOI: 10.1093/icvts/ivu334
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic treatment with coenzyme Q10 in patients undergoing cardiac surgery: could an antioxidant reduce complications? A systematic review and meta-analysis

Abstract: Coenzyme Q10 (CoQ10) is a lipid-soluble antioxidant that could have beneficial effects in patients undergoing cardiac surgery with cardiopulmonary bypass. There is no clear evidence about its clinical effects or a systematic review published yet. We aimed to conduct a systematic review and meta-analysis of the literature to elucidate the role of coenzyme Q10 in preventing complications in patients undergoing cardiac surgery with cardiopulmonary bypass. We searched the PubMed Database using the following keywor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 16 publications
1
16
0
1
Order By: Relevance
“…Twelve patients (22.2%) in the control group and three patients (6.3%) in the CoQ 10 group had episodes of AF after 12 months of treatment (p = 0.02). [118] Similar results were obtained by other authors, concluding that CoQ 10 as adjuvant treatment in patients with HF may attenuate the incidence of AF. The exact mechanisms of the effect are still unclear, even if one of the possible explanations could be attributed to the reduction of serum levels of malondialdehyde (MDA) [119].…”
Section: Coq 10 and Atrial Fibrillationsupporting
confidence: 83%
“…Twelve patients (22.2%) in the control group and three patients (6.3%) in the CoQ 10 group had episodes of AF after 12 months of treatment (p = 0.02). [118] Similar results were obtained by other authors, concluding that CoQ 10 as adjuvant treatment in patients with HF may attenuate the incidence of AF. The exact mechanisms of the effect are still unclear, even if one of the possible explanations could be attributed to the reduction of serum levels of malondialdehyde (MDA) [119].…”
Section: Coq 10 and Atrial Fibrillationsupporting
confidence: 83%
“…These authors interpreted the results to indicate a significant reduction in systolic blood pressure without improvements in other CVD risk factors, such as diastolic blood pressure, total cholesterol, LDL- and high-density lipoprotein (HDL)-cholesterol, and triglycerides. A second meta-analysis explored the impact of CoQ 10 in the prevention of complications in patients undergoing cardiac surgery, and the results showed that CoQ 10 therapy lowers the need of inotropic drugs and reduces the appearance of ventricular arrhythmias after surgery (de Frutos et al, 2015 ).…”
Section: Coq 10 Supplementation In the Treatment Omentioning
confidence: 99%
“…This effect may be related to the documented fall in cardiac CoQ 10 levels in the aged heart [114]. A meta-analysis reviewed eight clinical trials and concluded that patients submitted to cardiopulmonary bypass have a decreased requirement for ionotropic drugs and a reduced chance of ventricular arrhythmia if receiving CoQ 10 supplementation [145].…”
Section: Agingmentioning
confidence: 99%